Targeting anti-fibrotic pathways in Crohn's disease – The final frontier?. (February 2019) - Ma, Christopher; Jairath, Vipul; Click, Benjamin; Hirota, Simon A.; Lu, Cathy; Parker, Claire E.; Rieder, Florian; ,
Abstract: Intestinal fibrosis with stricture formation affects up to half of patients with Crohn's disease (CD), resulting in impaired quality of life, increased risk of surgical intervention, and associated patient morbidity. The underlying pathophysiologic mechansisms responsible for initiating and perpetuating intestinal fibrosis are complex, dynamic, and implicate both inflammation-dependent and independent pathways. Previously thought to be an irreversible complication of long-standing inflammation unresponsive to medical therapy, fibrostenotic CD has been traditionally managed with endoscopic or surgical approaches. However, recent advances in our understanding of the humoral, cellular, and environmental pathways driving intestinal fibrosis has the potential to fundamentally change these management paradigms for CD-related strictures. Furthermore, the promise of fibrosis treatments in other organ systems has encouraged hope that anti-fibrotic treatment approaches for CD may be within reach. Here, we summarize the key breakthroughs in our molecular understanding of intestinal fibrosis, review current medical, endoscopic, and surgical treatment approaches to CD-related strictures, propose future directions for anti-fibrotic therapy in CD, and identify crucial research questions in this field that require additional investigation.